Biochar Production from Agricultural Waste for Sustainable Soil Management and Climate Change Mitigation: A Comprehensive Review - Dick Dick Maulana; Hee-Deung Park (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2026)
Climate change and land degradation threaten global ecology and food security. Biochar, produced via oxygen-limited thermochemical conversion of agricultural waste, offers a multifunctional solution. This narrative review with meta-analysis of quantitative outcomes (2010-2025 literature) synthesizes biochar production techniques, physicochemical properties, and sustainable agriculture applications, demonstrating biochar's critical role in soil health improvement and climate change mitigation. Studies were selected based on: (1) peer-reviewed English-language journals, (2) agricultural waste feedstocks, (3) quantitative soil/crop/environmental outcomes, (4) field-relevant research, and (5) methodological rigor. Recent research documents biochar's transformative effects on soil physical (water retention +18-25% in sandy soils), chemical (pH 7-11, CEC enhancement), and biological properties, particularly in degraded, acidic, or nutrient-poor soils. Performance depends on feedstock type (agricultural residues, woody biomass, manure), pyrolysis temperature (350-700°C), and residence time (0.5-4 hours). Field trials report yield increases of 10-340% (meta-analysis range), carbon sequestration of 3.7 t CO2eq/t stable biochar, and GHG reductions of 30-50% N2O and 12-25% CH4 across diverse soil-crop systems. Co-application with fertilizers/compost optimizes nutrient use efficiency, though performance varies by soil type and environment, necessitating site-specific strategies. Economic barriers, production costs, and carbon market access influence adoption. Critical gaps include long-term field data and mechanistic insights into biochar-soil-microbe interactions. Future priorities encompass engineered biochar (nanoparticle-modified for targeted functions), precision applications, and policy frameworks. Strategic, evidence-based deployment protocols will maximize benefits while acknowledging context-dependent limitations, quality variability, and trade-offs requiring careful management.